Reliability information to support decision making for e-Government projects - Faiz, Mohd Turan; Daniel Osezua, Aikhuele; Kartina, Johan (Association for Computing Machinery, 2017)
E-government implementations in developing countries still face difficulties, leading to a large failure ratio. This paper proposed an exponential-related function adopted in an intuitionistic Fuzzy TOPSIS model for improving the understanding of failure and for building appropriate reliability knowledge to support decision making for e-government projects. The new method which is simple and straightforward have been successfully applied by virtue of numerical case studies for detecting failures, which in turn has provided information for building reliability knowledge to support decision making process. The method has been compared successfully with some similar computational approach in literature.